Health behaviour changes after type 2 diabetes diagnosis: Findings from the English Longitudinal Study of Ageing. Issue 1 (December 2018) - Hackett, Ruth; Moore, Catherine; Steptoe, Andrew; Lassale, Camille
Abstract Healthy lifestyle is key for type 2 diabetes (T2D) management. It is unclear whether individuals change health behaviours in response to T2D diagnosis. We compared smoking, physical activity, fruit and vegetable intake and alcohol consumption at three times (pre-diagnosis, at diagnosis, 2–4 years post-diagnosis) in individuals who developed T2D and controls. Behaviours were assessed in 6877 individuals at waves 3–7 of the English Longitudinal Study of Ageing. Generalized estimating equations were used to examine differences by group and time and group-by-time interactions. The T2D group were less active (p < 0.001) and consumed less alcohol (p < 0.001). Smoking (p < 0.001), alcohol consumption (p = 0.037) and physical activity (p = 0.042) decreased over time in the overall sample, fruit and vegetable intake (p = 0.012) and sedentary activity (p < 0.001) increased. A group-by-time interaction was found for smoking, with the T2D group having greater reductions in smoking over time (p < 0.001). No significant interactions were detected for other behaviours. We found limited evidence that T2D diagnosis encourages behaviour change, other than a reduction in smoking. Given the importance of lifestyle for T2D outcomes, strategies for motivating behaviour change need to be identified.